Seeds of destruction: the globalization of cotton as a result of the American Civil War - Calhoun, Ricky-Dale (Kansas State University, 2012)
Cotton was the most important commodity in the economy of the industrialized Western world in the mid-nineteenth century, as vital then as petroleum is today. It was widely believed that a prolonged interruption of the cotton supply would lead not merely to a severe economic depression, but possibly to the collapse of Western Civilization. Three quarters of the world’s cotton supply came from the Southern states of the United States. When the American Civil War erupted and cotton supplies were cut off, the British Cotton Supply Association was faced with the difficult task of establishing cotton cultivation in other locations. In order for the effort to succeed, the British had to obtain and distribute millions of pounds of American cotton seeds. The United States government, the Illinois Central Railroad, and a number of organizations and individuals cooperated to obtain the necessary seeds that the British had to have. American farm equipment manufacturers assisted by designing, making, and distributing portable cotton gins and other implements needed by cotton growers overseas. U.S. consuls overseas sometimes assisted the Cotton Supply Association with seed and equipment distribution. This dissertation is about the implementation of the grand economic strategies of the United States and Great Britain. It is also about the people who implemented those strategies on the ground, people as diverse as Union agents who went into Confederate territory to procure cotton seeds, farmers in Illinois, British consuls who distributed seeds grown in Illinois to farmers in the Ottoman Empire, and English colonists who flocked to Fiji with high hopes of becoming cotton planters. It attempts to measure the impact of the cotton boom and subsequent bust that resulted from the American Civil War on societies around the world.
Keywords: Civil War; Cotton; Ottoman Empire; Balkans; Egypt; Palestine; American History (0337); World History (0506)